Analysis of combustion concepts in a newly designed two-stroke high-speed direct injection compression ignition engine. (January 2015) - Benajes, Jesús; Novella, Ricardo; De Lima, Daniela; Tribotté, Pascal
Two research paths are being followed to develop compression ignition engines, the extreme optimization of the conventional diesel combustion concept and the development of alternative combustion concepts. The optimization of the conventional diesel combustion concept focuses on controlling the combustion development in an attempt to improve pollutant emissions and efficiency. Additionally, extensive research in four-stroke engines already demonstrated the benefits of the partially premixed combustion concept in terms of emissions and efficiency when using high volatility and low reactivity fuels, such as gasoline-like fuels, from medium-to-high engine loads. A detailed optimization of the conventional diesel combustion concept has been performed in an innovative two-stroke poppet valves high speed direct injection compression ignition engine, in order to find the real limits of this engine configuration. Later, its compatibility with the partially premixed combustion concept using a high octane fuel (Research Octane Number 95) with a triple injection strategy for reducing pollutant emissions at medium-to-low load conditions has been evaluated considering also the impact on engine efficiency. Results confirm the potential for attaining state-of-the-art emission levels operating with diesel combustion, and how emissions and efficiency can be optimized by adjusting the air management settings without facing any additional trade-off aside from that usual between NOX and soot. The feasibility of combining this engine configuration with the gasoline partially premixed combustion concept for controlling pollutant emissions has been also corroborated and, with a fine tuned triple injection strategy, engine efficiency even improves compared to that obtained operating with well-optimized diesel combustion.